2019
DOI: 10.1136/vr.105327
|View full text |Cite
|
Sign up to set email alerts
|

Rhodococcus equi‐specific hyperimmune plasma administration decreases faecal shedding of pathogenic R. equi in foals

Abstract: Rhodococcus equi is the most common cause of pneumonia in young foals. Pneumonic foals are an important source of environmental contamination as they shed higher amounts of R. equi in their faeces than unaffected foals. As R. equi-specific hyperimmune plasma (HIP) lessens clinical pneumonia, we hypothesise that its use would result in decreased faecal shedding of R. equi by foals. Neonatal foals were either given HIP (n=12) or nothing (n=9, control) shortly after birth and were then experimentally infected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Transfusion of R. equi hyperimmune plasma was reported to decrease shedding of R. equi in infected foals. 175 Although virulent R. equi appear to be ubiquitous in the faeces, air, and soil at horse-breeding farms, 1,2,10,[22][23][24][25]29 evidence exists that airborne concentrations of virulent R. equi are associated with the odds of pneumonia in foals at levels of both farm 10 and individual foal. [176][177] Thus, reducing the environmental burden of R. equi might be an important and complementary benefit of transfusion of hyperimmune plasma for mitigating rhodococcal pneumonia in foals.…”
Section: Transfusion Of Hyperimmune Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…Transfusion of R. equi hyperimmune plasma was reported to decrease shedding of R. equi in infected foals. 175 Although virulent R. equi appear to be ubiquitous in the faeces, air, and soil at horse-breeding farms, 1,2,10,[22][23][24][25]29 evidence exists that airborne concentrations of virulent R. equi are associated with the odds of pneumonia in foals at levels of both farm 10 and individual foal. [176][177] Thus, reducing the environmental burden of R. equi might be an important and complementary benefit of transfusion of hyperimmune plasma for mitigating rhodococcal pneumonia in foals.…”
Section: Transfusion Of Hyperimmune Plasmamentioning
confidence: 99%
“…R. equi in infected foals 175 . Although virulent R. equi appear to be ubiquitous in the faeces, air, and soil at horse‐breeding farms, 1,2,10,22–25,29 evidence exists that airborne concentrations of virulent R. equi are associated with the odds of pneumonia in foals at levels of both farm 10 and individual foal 176–177 .…”
Section: Preventionmentioning
confidence: 99%
“…In addition to reducing the incidence of clinical and subclinical pneumonia, transfusion of RE hyperimmune plasma may aid in controlling R. equi by reducing environmental exposure. 76,77 Airborne concentrations of virulent R. equi have been associated with increased odds of pneumonia at the level of farm 16 and individual foal. 6,70 As noted above, foals are exposed to R. equi in their environment from birth.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…In a study summarised on p 19 of this issue of Vet Record, Sanz and colleagues investigated the clinical eicacy of HIP in foals experimentally infected with R equi. 18 By analysing faecal samples collected during the course of the study, they found that HIP administration decreases faecal shedding of virulent R equi in treated foals. This inding has implications for disease control as the lower faecal shedding by HIPtreated foals would decrease environmental contamination, and may, therefore, reduce R equi transmission.…”
Section: Research Commentmentioning
confidence: 99%
“…Despite their variable efficacy and relatively high cost, HIP products are widely used to manage R equi pneumonia, and research into their protective effect is ongoing. In a study summarised on p 19 of this issue of Vet Record , Sanz and colleagues investigated the clinical efficacy of HIP in foals experimentally infected with R equi 18 . By analysing faecal samples collected during the course of the study, they found that HIP administration decreases faecal shedding of virulent R equi in treated foals.…”
mentioning
confidence: 99%